Cyberknife Treatment for Low and Intermediate Risk Prostate Cancer. (28th May 2015) - Detti, B.; Bonomo, P.; Masi, L.; Doro, R.; Cipressi, S.; Iermano, C.; Bonucci, I.; Franceschini, D.; Di Cataldo, V.; Di Brina, L.; Baki, M.; Simontacchi, G.; et al.
<x xml:space="preserve">Abstract</x> Cyberknife is an emerging treatment for early stage prostate cancer. Between October 2012 and January 2014, 32 patients were treated in our institution. Prescribed dose was 35–36.25 Gy in five fractions. Biochemical response was observed in 22 patients. Four patients experienced G2 acute genitourinary toxicity and in two cases we recorded G3 acute GU toxicity. 5 patients experienced G2 acute proctitis. At last follow up visit, all patients were still alive. 29 remained free of disease at last follow up appointment, while three developed a biochemical recurrence. Our experience confirms the efficacy and safety of Cyberknife for localized prostate cancer.